2011
DOI: 10.1039/c1cc12569a
|View full text |Cite
|
Sign up to set email alerts
|

Little exchange at the liquid/solid interface: defect-mediated equilibration of physisorbed porphyrin monolayers

Abstract: w This article is part of the ChemComm 'Molecule-based surface chemistry' web themed issue. z Electronic supplementary information (ESI) available: Experimental procedures, detailed analysis of the M and B unit cells by STM and molecular models, (TUP)Co insertion data, and additional STM images of the annealing process in time. See

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
45
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(50 citation statements)
references
References 26 publications
(5 reference statements)
4
45
1
Order By: Relevance
“…54 They observed the behavior of monolayers of copper 5,10,15,20tetraundecylporphyrin ((TUP)Cu, Fig. 54 They observed the behavior of monolayers of copper 5,10,15,20tetraundecylporphyrin ((TUP)Cu, Fig.…”
Section: Strong Kinetic Controlmentioning
confidence: 96%
“…54 They observed the behavior of monolayers of copper 5,10,15,20tetraundecylporphyrin ((TUP)Cu, Fig. 54 They observed the behavior of monolayers of copper 5,10,15,20tetraundecylporphyrin ((TUP)Cu, Fig.…”
Section: Strong Kinetic Controlmentioning
confidence: 96%
“…Different 2D polymorphs of Cu−C 11 P have been produced by varying the porphyrin concentration in the supernatant solution, with higher-coverage polymorphs forming at higher solution concentrations (51,52). Increasing the porphyrin concentration once a SAM has formed brings about dynamic changes to the SAM only around defects, however, indicating that the SAMs are kinetically trapped, and this trapping takes only seconds to manifest after first application of the solution to the substrate.…”
mentioning
confidence: 99%
“…This means that the relative abundance of the polymorphs on the surface is completely governed by kinetics. We found that transformation of domains from one polymorph to another can only occur at specific defect sites in the physisorbed layer 33. Domains lacking these defects were found to be unable to adapt to a changing composition of the supernatant for timescales of at least hours to days.…”
Section: Introductionmentioning
confidence: 89%
“…Self‐assembled molecular networks of (TUP)Cu on HOPG are, in many cases, not in thermodynamic equilibrium with the supernatant solution 33. We observed that adsorption of the molecules at the interface, upon application of the solution to the surface, is a fast process (on the order of seconds), whereas their desorption is extremely slow.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation